Renal function in Thalassemia major patients who treated by Desferal (Bangladesh Journal of Medical Science, 2018)
Background and purpose: β-thalassemia is the most common inherited hemoglobinopathy in all over the world. Iron over load will be appearing in kidney following blood transfusion. Desferal is one of iron chelator that can be ended renal complication. The aim of this study is evaluation the renal function in β- Thalassemia patients who were treated by Desferal.Materials and methods: in this descriptive and analytic study 40 thalassemia patients who were treated by Desferal and 40 non Thalassemia subjects enrolled in this study randomly. For evaluation the renal function in these groups, we measured the Cr, BUN, K, Na, Uric acid, β-2 globin, Ca, Mg, P and Urea of blood and Na, K, Cr, protein and volume of urine 24 hours. We compared these variables between two groups. Also descriptive and analytic analyses were used, the significant level in this study was p≤0.05.Results: comparing the renal function between two groups show that; the level of Na, Ca, K and β-2 Globin in serum and Cr, protein and urine volume in 24 hours had significant difference.Conclusion: renal dysfunction such as; glomerular and tubular dysfunction and reduced filtration capacity are common in β-thalassemia patients.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.58-61